Dini duygular mizah karşısında korunur mu? (İHAS sistemi kapsamında bir inceleme) - Polat Goral, Betül (My University, 2024)
Mizahi ifade özgürlüğü, mizahın karmaşık yapısı nedeniyle olsa gerek hukuki incelemelere çok az konu olmuştur. İnsan Hakları Avrupa Mahkemesi içtihadı ve literatürü ise mizahi ifade özgürlüğünü anlamak bakımından yetersiz kalmaktadır. Bu sebeple mizahi ifade özgürlüğü kararlarında, bilhassa dini duyguların korunmasına ilişkin içtihatlarda istikrarsızlık söz konusu olmaktadır. Eldeki çalışma mizahi ifade özgürlüğü alanındaki içtihadi yetersizliğin nedenlerini ve dini duygular söz konusu olduğunda içtihattaki değişimleri ortaya çıkarmayı amaçlamaktadır. Üç bölümden oluşan çalışmanın birinci bölümünde “mizah” kavramı ve “mizahi ifadeler” öğreti ve insan hakları hukuku açısından ele alınmaktadır. İkinci bölümde bu kez “din” kavramı ve “dini duygular” öğreti ve insan hakları hukuku açısından incelenmektedir. Üçüncü ve son bölümde mizahi ifade özgürlüğünün sınırlandırma ölçütleri tespit edilmekte ve bu ölçütler dini duygular karşısında sınamaya tabi tutulmaktadır.

The freedom of humorous expression, perhaps due to the complex nature of humor, has rarely been the subject of legal scrutiny. The jurisprudence and literature of the European Court of Human Rights are insufficient in understanding the freedom of humorous expression. Therefore, there is inconsistency in the decisions regarding the freedom of humorous expression, especially in the jurisprudence related to the protection of religious feelings. This study aims to uncover the reasons behind the inadequacy of jurisprudence in the field of humorous expression freedom and the changes in jurisprudence when religious feelings are involved. The study, which consists of three parts, addresses the concept of “humor” and “humorous expressions” from the perspective of doctrine and human rights law in the first part. In the second part, the concept of “religion” and “religious feelings” are examined from the perspective of doctrine and human rights law. In the third and final part, the criteria for limiting the freedom of humorous expression are identified and subjected to testing against religious feelings.
Are religious feelings protected against humour?(an analysis within the scope of the ECHR system)
Keywords: Din ve devlet; Dini Duygular; Dini yönleri; European Court of Human Rights; Freedom of Humorous Expression; Freedom of religion; Humour; İnanç özgürlüğü; İnsan Hakları Avrupa Mahkemesi; Liberty; Mizah; Mizahi İfade Özgürlüğü; Özgürlük; Religion and state; Religious aspects; Religious Feelings